Solid State Fermentation Of Gibberellic Acid By Penicillium Variable: Screening, Optimization And Kinetic Studies - Isa, Nur Kamilah Md (2013)
Gibberellic acid (GA3) is one of the family members of gibberellins that have wider applications toward plant growth acceleration. A normal plant can only produce growth hormone in a very small quantity, but with sufficient addition of GA3 could affect the growth development of plant organs. A few sources of substrates were evaluated for their capabilities as a growth medium for the production of GA3 in solid state fermentation (SSF). Banana peel (BP) was found as a suitable substrate as it contain higher amount of carbon and lower amount of nitrogen source at 44.85 % ± 0.15 and 12.16 % ± 0.16, respectively. In the present study, sixteen macro- and micro-fungi from different families (Polyporaceae, Coriolaceae, Lentinaceae, Schizophyllaceae, Trichocomaceae, Hypocreaceae, and Moniliaceae) were screened for the production of GA3 using BP as a substrate. It is found that P. variable produced the highest GA3 followed by A. niger, P. simplicissimum and P. spinulosum at 16.25 ± 0.06 mg/kg substrate, 12.45 ± 0.11 mg/kg substrate, 5.56 ± 0.06 mg/kg substrate and 3.90 ± 0.06 mg/kg substrate, respectively.